LINGUISTIC ANALYSIS OF THE WORD - Fayzullayeva Dilnoza Ubaydulloyevna (European Journal of Humanities and Educational Advancements, 2022)
This article deals with the linguistic analysis of the word. There is also a study of linguistic analysis in terms of language, units of speech, its components, content, function and other features, the definition of the exact state of units of language (speech)